Effect of salbutamol-based anti-asthmatic medication on surface roughness and color stability of different types of hybrid ceramics - Noha Attia; Waleed Elshahawy; Abeer Atef Younes (BDJ Open)
Abstract Objective To evaluate the impact of salbutamol sulfate inhalation on the surface roughness and color stability of hybrid ceramics using an inhaler and nebulizer at different doses over three time periods. Materials and methods A total of 120 samples of Lava Ultimate (LU), Cerasmart (CS), and Nacera Hybrid (NH) were divided into three equal groups. Each group was subdivided into two subgroups according to the use of inhaler or nebulizer. Each subgroup was subdivided into two divisions according to the minimum and maximum doses of inhalation. The samples were cut rectangular and polished according to the manufacturers’ instructions. They were exposed to salbutamol in acrylic boxes and then kept in artificial saliva for 30, 60, and 90 days which was equivalent to 4, 8, and 12 months. The surface roughness and color change (ΔE) were measured before and after exposure to salbutamol via a non-contact profilometer and a reflective spectrophotometer based on CIE L*a*b* respectively. The data were tabulated and statistically analysed using a three-way ANOVA test and the significance level was set at P ≤ 0.05. Results Cerasmart recorded the highest statistically non-significant roughness change (1.2298 ± 0.331%, P > 0.05). NH had the highest statistically significant ΔE (ΔE = 6.174, P ≤ 0.0001). The maximum dose used in three-month exposure period had the highest statistically significant change in roughness and color (P ≤ 0.0001). Additionally, the inhaler-treated groups presented significantly higher values than the nebulizer-treated groups for ΔE only (P < 0.05). Eventually, Pearson correlation analysis revealed a statistically significant positive direct relationship between roughness and ΔE (P = 0.013). Conclusions Salbutamol can significantly affect the color of hybrid ceramics while causing a non-significant increase in their surface roughness.